High-conductivity halogen-free flame-retardant polyurethane sponge as well as preparation method and application thereof

The halogen-free flame-retardant polyurethane sponge addresses uniform dispersion issues by forming a composite connection structure with nano-semiconductor particles and expanded graphite, ensuring conductivity, flame retardancy, and mechanical strength, while maintaining performance stability under varying conditions.

CN119176927AActive Publication Date: 2024-12-24DONGGUAN PEIWEN NEW MATERIAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411296459.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-24
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Existing polyurethane sponges face challenges in achieving uniform dispersion of conductive and flame retardant materials, which leads to reduced conductivity, flame retardancy, and mechanical strength, while also struggling with performance stability under varying environmental conditions.

Method used

A highly conductive halogen-free flame-retardant polyurethane sponge is prepared using a specific composition of polyether polyol, polypropylene glycol, polytetramethylene ether, polyisocyanate, modified functional particles, flame retardant, epoxy block, and catalyst, forming a composite connection structure with nano-semiconductor particles and expanded graphite interlayer, enhanced by a stable composite structure and epoxy block's double-layer membrane wrapping effect.

Benefits of technology

The sponge maintains excellent conductivity, flame retardancy, mechanical strength, and aging resistance, improving its performance under humid conditions and preventing filler detachment, with enhanced electron flow and water penetration resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005046184340000171
    Figure BDA0005046184340000171
Patent Text Reader

Abstract

The invention relates to the field of sponge materials, in particular to high-conductivity halogen-free flame-retardant polyurethane sponge as well as a preparation method and application thereof. The high-conductivity halogen-free flame-retardant polyurethane sponge is prepared from the following raw materials in parts by mass: 40 to 50 parts of polyether polyol, 20 to 30 parts of polypropylene glycol, 5 to 15 parts of polytetrahydrofuran ether, 50 to 70 parts of polyisocyanate, 1 to 4 parts of deionized water, 5 to 15 parts of modified functional particles, 5 to 10 parts of a flame retardant, 5 to 10 parts of an epoxy block, 1 to 2 parts of a catalyst and 5 to 15 parts of an auxiliary agent. The polyurethane sponge prepared by the invention can maintain good waterproof, mechanical, temperature-resistant and aging-resistant properties on the premise of ensuring excellent conductivity and flame retardance, the application performance of the polyurethane sponge is greatly improved, the deficiency of waterproof, mechanical and other properties caused by the addition of functional filler is avoided, and the application prospect is wide. And the method has a very excellent market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sponge materials, and in particular to a highly conductive halogen-free flame-retardant polyurethane sponge and a preparation method and application thereof. Background Art

[0002] Conductive polyurethane sponge, as a new type of functional material, has received extensive attention in recent years. This material combines the softness of polyurethane sponge with the electrical properties of conductive fillers, making it have broad application prospects in electronic devices, electromagnetic interference (EMI) shielding, electrostatic discharge (ESD) protection, sensor devices and smart textiles.

[0003] Polyurethane sponge is a porous material formed by complex chemical reactions of polyisocyanates and polyols. It has excellent compression resilience, sound absorption, heat preservation and good mechanical strength. However, unmodified polyurethane sponge itself does not have conductivity, which limits its application in the electronics industry. In order to give polyurethane sponge conductivity, a common practice is to add various conductive fillers during the preparation process, such as carbon black, graphite, metal powder, graphene, carbon nanotubes (CNTs), conductive polymers such as polyaniline (PANI), etc. These raw materials form a conductive network in the polyurethane matrix, thereby achieving effective charge transfer.

[0004] However, in the prior art, polyurethane sponges still have some technical problems. For example, the uniform dispersion of conductive raw materials or flame retardant raw materials in the polyurethane matrix is ​​a major difficulty. The agglomeration of fillers will not only reduce the conductivity and flame retardancy, but also may weaken the mechanical properties of the sponge. While pursuing high conductivity and flame retardancy, how to maintain the mechanical strength, elasticity and durability of the sponge becomes a key issue. The functional fillers contained in the sponge often damage the original properties of the sponge. The performance stability of conductive polyurethane sponges under different environmental conditions, such as in an environment with high humidity, is also a research focus, especially whether they can maintain their own stability under extreme conditions.

[0005] Therefore, in order to solve the above problems, the present application provides a highly conductive halogen-free flame-retardant polyurethane sponge and a preparation method thereof. The polyurethane sponge prepared in the present application can retain good waterproof, mechanical, heat-resistant and aging-resistant properties while ensuring excellent conductive and flame-retardant properties, thereby greatly improving the application performance of the polyurethane sponge and avoiding the loss of waterproof, mechanical and other properties due to the addition of functional fillers, and has very excellent market application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a highly conductive halogen-free flame-retardant polyurethane sponge. The raw materials include, by mass: 40 to 50 parts of polyether polyol, 20 to 30 parts of polypropylene glycol, 5 to 15 parts of polytetramethylene ether, 50 to 70 parts of polyisocyanate, 1 to 4 parts of deionized water, 5 to 15 parts of modified functional particles, 5 to 10 parts of flame retardant, 5 to 10 parts of epoxy block, 1 to 2 parts of catalyst, and 5 to 15 parts of additives.

[0007] As a preferred solution, the mass ratio of the polyether polyol, polypropylene glycol, polytetramethylene ether and polyisocyanate is (4-4.5): (2-2.5): (1-1.5): (5.5-6.5).

[0008] As a preferred solution, the mass ratio of the polyether polyol, polypropylene glycol, polytetramethylene ether and polyisocyanate is (4.2-4.5): (2.2-2.5): (1-1.2): (5.8-6.4).

[0009] As a preferred solution, the mass ratio of the polyether polyol, the modified functional particles and the epoxy block is (4-4.5): (1-1.4): (0.6-1).

[0010] As a preferred solution, the polyether polyol is at least one of polyoxypropylene polyol, polyoxypropylene / ethylene oxide copolymer polyol, glyceryl polyether polyol, and tetrahydrofuran-propylene oxide copolymer polyol.

[0011] As a preferred solution, the functionality of the polyether polyol is 3.

[0012] As a preferred solution, the weight average molecular weight of the polyether polyol is 4500-7000 g / mol.

[0013] As a preferred solution, the weight average molecular weight of the polyether polyol is 5000-6000 g / mol.

[0014] As a preferred solution, the weight average molecular weight of the polypropylene glycol is 2000-3000 g / mol.

[0015] As a preferred embodiment, the polytetrahydrofuran ether is polytetrahydrofuran diol.

[0016] As a preferred solution, the weight average molecular weight of the polytetrahydrofuran ether is 1000-1500 g / mol.

[0017] As a preferred solution, the polyisocyanate is at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, cyclohexane diisocyanate, and xylylene diisocyanate.

[0018] As a preferred solution, the polyisocyanate is 2,4'-diphenylmethane diisocyanate.

[0019] As a preferred solution, the preparation method of the modified functional particles comprises the following steps: S1: adding expandable graphite and titanium dioxide to water, adding petroleum calcium sulfonate and succinic anhydride, heating to 60-70°C, ultrasonically dispersing uniformly, stirring at a speed of 60-120 r / min for reaction for 2-3 hours, and adding 3-aminopropyltriethoxysilane dropwise 0.5 hours before the reaction to obtain pretreated particles; S2: adding the pretreated particles and trimesic acid to a DMF solution, stirring uniformly, and ultrasonically dispersing for 10-15 minutes. n obtain a mixed solution, then drop the DMF solution containing copper acetate into the mixed solution, the dropping temperature is 50-60°C, the dropping is accompanied by stirring at a speed of 200-300r / min, the dropping time is 1-1.5h, after the dropping is completed, the reaction is transferred to a high-pressure reactor and heated to 120-130°C for 14-20h; S3: after the reaction is completed, triethanolamine is added, the mixture is stirred for 0.5-1h, the product is centrifuged and filtered, and methanol washing and 80-90°C vacuum drying are repeated for multiple times, and the product is obtained after completion.

[0020] As a preferred solution, the mass ratio of expandable graphite, titanium dioxide, calcium petroleum sulfonate, succinic anhydride and 3-aminopropyltriethoxysilane is (2-3): (0.5-1): (0.4-0.8): (1-1.5): (0.1-0.3).

[0021] As a preferred solution, the mass ratio of expandable graphite, titanium dioxide, calcium petroleum sulfonate, succinic anhydride and 3-aminopropyltriethoxysilane is (2-2.5): (0.6-0.8): (0.4-0.6): (1.2-1.4): (0.2-0.3).

[0022] As a preferred solution, the average particle size of the titanium dioxide is 10 to 30 nm.

[0023] As a preferred solution, the average particle size of the expandable graphite is 4 to 8 μm.

[0024] As a preferred solution, the mass ratio of the pretreated particles, trimesic acid, copper acetate and triethanolamine is (3.5-4): (0.4-0.8): (1.2-2): (0.4-0.6).

[0025] In the present application, the addition of the above-mentioned modified functional particles can ensure that the polyurethane sponge has excellent electrical conductivity and flame retardancy, while having good waterproof, aging resistance and mechanical properties, effectively solving the performance deficiency problem existing in the prior art. The added modified functional particles can form a composite connection structure of nano-semiconductor particles, framework particle structure and expanded graphite interlayer structure, the existence of which can be connected by coordination and hydrogen bonds after modification of surface groups, while greatly enhancing the connection strength between them, providing a great convenience space for the formation of electronic connection paths, thereby greatly improving the flow path length and flow speed of electrons in the sponge system, and can also enhance the connection strength of expandable graphite and organic sponge through the connection between the groups on the surface of the particles and the organic sponge, avoiding the migration of conductive particles, thereby ensuring that the conductivity and flame retardancy of expandable graphite are not reduced due to the detachment of fillers during long-term use.

[0026] On the other hand, the added modified functional particles can play a good linear support role when external forces act through their stable composite structure and their connection function with the organic sponge system, especially when stretched, the connection between the particles and the sponge system greatly improves its strength; and the composite structure of the modified functional particles can form a good rough peak-valley structure on the surface of the organic sponge through its low surface energy and high roughness surface. The hydrophobic property of this structure and the framework particles can greatly reduce the formation speed of the hydration layer on the surface of the organic sponge, and can produce local adsorption in the process of contact with water molecules in a short time. Before adsorption saturation, it can greatly increase the penetration resistance of water molecules to the organic sponge, increase the penetration path length, and thus improve the waterproof performance. And its stable composite structure can effectively adsorb active molecules and groups inside the organic sponge system, thereby greatly removing the reactive molecules in the sponge system, thereby avoiding the aging reaction due to the influence of temperature and moisture during long-term use, and thus obtaining excellent aging resistance.

[0027] As a preferred solution, the flame retardant is a combination of ammonium polyphosphate and zinc borate.

[0028] As a preferred solution, the mass ratio of the ammonium polyphosphate to the zinc borate is (4-8):(2-4).

[0029] As a preferred solution, the mass ratio of the ammonium polyphosphate to the zinc borate is (6-8):(2-3).

[0030] As a preferred solution, the epoxy block is a block copolymer of ethylene oxide and propylene oxide.

[0031] As a preferred solution, the epoxy block material is a composition of an epoxy block material with a weight average molecular weight of 1000 to 2000 g / mol and an epoxy block material with a weight average molecular weight of 4000 to 5000 g / mol.

[0032] As a preferred solution, the mass ratio of the epoxy block with a weight average molecular weight of 1000-2000 g / mol to the epoxy block with a weight average molecular weight of 4000-5000 g / mol is (1-1.5):(3-4).

[0033] In this application, the waterproof, mechanical and aging resistance of polyurethane sponge are greatly improved by the compounding effect of the above-mentioned epoxy block and the added polyol raw material. The added epoxy block can preferentially form a double-layer membrane wrapped structure formed by different molecular weight phases with the added modified functional particles. The existence of this structure can greatly improve the dispersion flow effect of the modified functional particles in its system after adding the polyol system, and then effectively avoid the agglomeration phenomenon inside the sponge system in the mixing stage; and the added epoxy block can improve the paving effect of the modified functional particles in the sponge reaction system through the guiding effect of its molecular chain, so that the modified functional particles and the polyurethane sponge system not only have good adsorption effect, but also can play a good embedding effect. On the other hand, different length molecular chains can play a good guiding role for the modified functional particles in the polyol system to different degrees, thereby increasing the exposed area of ​​the modified functional particles on the sponge surface and inside the pores while enhancing the strength of the three-dimensional network construction inside the polyurethane sponge system, thereby greatly enhancing the flame retardant, waterproof and aging resistance of the polyurethane sponge.

[0034] As a preferred solution, the catalyst is at least one of dibutyltin dilaurate, triethylenediamine, triethylenediamine, liquid alcohols, ethylenediamine, triethylamine, and trioctylamine.

[0035] As a preferred solution, the auxiliary agent at least includes an auxiliary foaming agent and a surfactant.

[0036] As a preferred solution, the auxiliary foaming agent is any one of cyclopentane, supercritical carbon dioxide, and sodium bicarbonate.

[0037] As a preferred solution, the surfactant is at least one of lauryl alcohol polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, alkyl glycoside, and betaine.

[0038] As a preferred solution, the mass ratio of the foaming agent to the surfactant is (0.5-2):(6-10).

[0039] The second aspect of the present application provides a method for preparing the above-mentioned highly conductive halogen-free flame-retardant polyurethane sponge, comprising the following specific steps: S1: mixing the modified functional particles and the epoxy block in a high-speed mixer at 200-300 rpm for 30-40 minutes and then taking them out together, then mixing them with polyether polyol, polypropylene glycol, polytetramethylene ether, deionized water, flame retardant, catalyst and additives, stirring at a speed of 60-120 rpm for 20-40 minutes to mix evenly; S2: adding polyisocyanate and stirring at a speed of 1500-2000 rpm for 3-5 minutes, placing the stirred mixture into a sponge mold, controlling the mold temperature at 30-35°C, keeping it warm for 20-25 hours, washing and cutting after completion, and obtaining the sponge.

[0040] The third aspect of the present application provides an application of the above-mentioned highly conductive halogen-free flame-retardant polyurethane sponge in electronic devices, electromagnetic interference shielding, electrostatic discharge protection, sensor devices and smart textiles.

[0041] The beneficial effects of this application are:

[0042] 1. The present application provides a highly conductive halogen-free flame-retardant polyurethane sponge, which can retain good waterproof, mechanical, heat-resistant and aging-resistant properties while ensuring excellent conductive and flame-retardant properties, thereby greatly improving the application performance of the polyurethane sponge and avoiding the loss of waterproof, mechanical and other properties due to the addition of functional fillers, and has very excellent market application prospects.

[0043] 2. A highly conductive halogen-free flame-retardant polyurethane sponge provided in the present application, wherein the added modified functional particles can form a composite connection structure of nano-semiconductor particles, framework particle structure and expanded graphite interlayer structure, wherein the existence of this structure can be connected through coordination and hydrogen bonds after modification of surface groups, which greatly enhances the connection strength therebetween and provides a great convenience for the formation of electronic connection pathways, thereby greatly improving the flow pathway length and flow velocity of electrons in the sponge system, and can also enhance the connection strength of expandable graphite and organic sponge through the connection between the groups on the surface of the particles and the organic sponge, thereby avoiding the migration of conductive particles, thereby ensuring that the conductivity and flame retardant properties of the expandable graphite are not reduced due to the detachment of the filler during long-term use.

[0044] 3. A highly conductive halogen-free flame-retardant polyurethane sponge provided in the present application, the added modified functional particles can play a good linear supporting role when external force acts through their stable composite structure and their connection function with the organic sponge system, especially under tension, the connection between the particles and the sponge system greatly improves its strength; and the composite structure of the modified functional particles can form a good rough peak-valley structure on the surface of the organic sponge through its lower surface energy and high roughness surface. The hydrophobic property of this structure and the framework particles can greatly reduce the formation speed of the hydration layer on the surface of the organic sponge, and can produce local adsorption in the process of contact with water molecules in a short time. Before adsorption saturation, it can greatly increase the penetration resistance of water molecules to the organic sponge, increase the penetration path length, and thus improve the waterproof performance.

[0045] 4. A highly conductive halogen-free flame-retardant polyurethane sponge provided in the present application greatly improves the waterproof, mechanical and aging resistance of the polyurethane sponge through the compounding effect of the epoxy block and the added polyol raw material; the added epoxy block can preferentially form a double-layer membrane wrapping structure formed by different molecular weight phases with the added modified functional particles, and the existence of this structure can greatly improve the dispersion flow effect of the modified functional particles in its system after the addition of the polyol system, thereby effectively avoiding the agglomeration phenomenon inside the sponge system during the mixing stage; and the added epoxy block can improve the paving effect of the modified functional particles in the sponge reaction system through the guiding effect of its molecular chain, so that the modified functional particles and the polyurethane sponge system not only have a good adsorption effect, but also have a good embedding effect. DETAILED DESCRIPTION

[0046] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0047] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0048] Example 1

[0049] Example 1 The first aspect provides a highly conductive halogen-free flame-retardant polyurethane sponge. The raw materials include, by mass: 42.5 parts of polyether polyol, 24.4 parts of polypropylene glycol, 11.5 parts of polytetramethylene ether, 63.5 parts of polyisocyanate, 2.4 parts of deionized water, 12.5 parts of modified functional particles, 8.5 parts of flame retardant, 8.8 parts of epoxy block, 1.8 parts of catalyst, and 8.2 parts of additives.

[0050] The polyether polyol is polyoxypropylene triol with a functionality of 3 and a weight average molecular weight of 5000 g / mol, and is purchased from Suzhou Senfida Chemical Co., Ltd. as a product of the corresponding molecular weight.

[0051] The weight average molecular weight of polypropylene glycol is 2000 g / mol, which is a product of corresponding molecular weight purchased from Hai'an Petrochemical in Jiangsu Province; polytetrahydrofuran ether is polytetrahydrofuran diol with a weight average molecular weight of 1100 g / mol, which is a product of corresponding molecular weight purchased from Shandong Deyitai New Materials Co., Ltd.

[0052] The polyisocyanate is 2,4'-diphenylmethane diisocyanate.

[0053] The preparation method of modified functional particles comprises the following steps, calculated by mass: S1: 2.36 parts of expandable graphite and 0.72 parts of titanium dioxide are mixed and added to 120 parts of deionized water, 0.45 parts of petroleum calcium sulfonate and 1.28 parts of succinic anhydride are added, heated to 65°C and ultrasonically dispersed uniformly, stirred at a speed of 100 r / min for 3 hours, and 0.28 parts of 3-aminopropyltriethoxysilane are added dropwise 0.5 hours before the reaction to obtain pretreated particles; S2: 3.8 parts of pretreated particles and 0.65 parts of trimesic acid are mixed and added to 80 parts of DM The F solution was stirred evenly and ultrasonically dispersed for 15 minutes to obtain a mixed solution, and then a DMF solution containing 1.75 parts of copper acetate (20 parts in total) was added dropwise to the mixed solution. The dropping temperature was 60°C, and the dropping was accompanied by stirring at a speed of 200r / min. The dropping time was 1h. After the dropping was completed, the reaction was transferred to a high-pressure reactor and heated to 125°C for insulation reaction for 16h; S3: After the reaction was completed, 0.58 parts of triethanolamine was added, mixed and stirred for 1h, the product was centrifuged and filtered, and washed with methanol and vacuum dried at 80°C for 3 times. After completion, it was obtained.

[0054] The average particle size of titanium dioxide is 25 nm.

[0055] The average particle size of expandable graphite was 8.6 μm, which was purchased from Lingshou County Chengnuo Mineral Products Co., Ltd. and was ground twice.

[0056] The flame retardant is a composition of ammonium polyphosphate and zinc borate, and the mass ratio of the ammonium polyphosphate to the zinc borate is 6:2.5.

[0057] The epoxy block material is a block copolymer of ethylene oxide and propylene oxide, and the epoxy block material is a composition of BASF L42 (weight average molecular weight 1600 g / mol) and BASF L85 (weight average molecular weight 4600 g / mol), and the mass ratio of the two is 1.2:3.5.

[0058] The catalyst is dibutyltin dilaurate.

[0059] The auxiliary agents are auxiliary foaming agent and surfactant, and the mass ratio of the two is 1.1:7.1.

[0060] The surfactant was lauryl alcohol polyoxyethylene ether, which was purchased from the MOA-4 product sold by Haian Guoyun Chemical.

[0061] The auxiliary blowing agent is cyclopentane.

[0062] The second aspect of the present embodiment provides a method for preparing the above-mentioned highly conductive halogen-free flame-retardant polyurethane sponge, comprising the following specific steps: S1: mixing the modified functional particles and the epoxy block in a high-speed mixer at 250 rpm for 40 minutes and then taking them out together, and then mixing them with polyether polyol, polypropylene glycol, polytetramethylene ether, deionized water, flame retardant, catalyst and additives, and stirring at 100 rpm for 35 minutes to mix evenly; S2: adding polyisocyanate and stirring at 1800 rpm for 4 minutes, placing the stirred mixture into a sponge mold, controlling the mold temperature at 32.5°C, keeping it warm for 22 hours, and washing and cutting after completion.

[0063] Example 2

[0064] Example 2 The first aspect provides a highly conductive halogen-free flame-retardant polyurethane sponge. The raw materials include, by mass: 40 parts of polyether polyol, 25 parts of polypropylene glycol, 10 parts of polytetramethylene ether, 64.5 parts of polyisocyanate, 2.2 parts of deionized water, 10 parts of modified functional particles, 8.5 parts of flame retardant, 6.5 parts of epoxy block, 1.65 parts of catalyst, and 8.2 parts of additives.

[0065] The polyether polyol is polyoxypropylene triol with a functionality of 3 and a weight average molecular weight of 5000 g / mol, and is purchased from Suzhou Senfida Chemical Co., Ltd. as a product of the corresponding molecular weight.

[0066] The weight average molecular weight of polypropylene glycol is 2000 g / mol, which is a product of corresponding molecular weight purchased from Hai'an Petrochemical in Jiangsu Province; polytetrahydrofuran ether is polytetrahydrofuran diol with a weight average molecular weight of 1100 g / mol, which is a product of corresponding molecular weight purchased from Shandong Deyitai New Materials Co., Ltd.

[0067] The polyisocyanate is 2,4'-diphenylmethane diisocyanate.

[0068] The preparation method of modified functional particles comprises the following steps, calculated by mass: S1: 2.36 parts of expandable graphite and 0.72 parts of titanium dioxide are mixed and added to 120 parts of deionized water, 0.45 parts of petroleum calcium sulfonate and 1.28 parts of succinic anhydride are added, heated to 65°C and ultrasonically dispersed uniformly, stirred at a speed of 100 r / min for 3 hours, and 0.28 parts of 3-aminopropyltriethoxysilane are added dropwise 0.5 hours before the reaction to obtain pretreated particles; S2: 3.8 parts of pretreated particles and 0.65 parts of trimesic acid are mixed and added to 80 parts of DM The F solution was stirred evenly and ultrasonically dispersed for 15 minutes to obtain a mixed solution, and then a DMF solution containing 1.75 parts of copper acetate (20 parts in total) was added dropwise to the mixed solution. The dropping temperature was 60°C, and the dropping was accompanied by stirring at a speed of 200r / min. The dropping time was 1h. After the dropping was completed, the reaction was transferred to a high-pressure reactor and heated to 125°C for insulation reaction for 16h; S3: After the reaction was completed, 0.58 parts of triethanolamine was added, mixed and stirred for 1h, the product was centrifuged and filtered, and washed with methanol and vacuum dried at 80°C for 3 times. After completion, it was obtained.

[0069] The average particle size of titanium dioxide is 25 nm.

[0070] The average particle size of expandable graphite was 8.6 μm, which was purchased from Lingshou County Chengnuo Mineral Products Co., Ltd. and was ground twice.

[0071] The flame retardant is a composition of ammonium polyphosphate and zinc borate, and the mass ratio of the ammonium polyphosphate to the zinc borate is 6:2.5.

[0072] The epoxy block material is a block copolymer of ethylene oxide and propylene oxide, and the epoxy block material is a composition of BASF L42 (weight average molecular weight 1600 g / mol) and BASF L85 (weight average molecular weight 4600 g / mol), and the mass ratio of the two is 1.2:3.5.

[0073] The catalyst is dibutyltin dilaurate.

[0074] The auxiliary agents are auxiliary foaming agent and surfactant, and the mass ratio of the two is 1.1:7.1.

[0075] The surfactant was lauryl alcohol polyoxyethylene ether, which was purchased from the MOA-4 product sold by Haian Guoyun Chemical.

[0076] The auxiliary blowing agent is cyclopentane.

[0077] The second aspect of the present embodiment provides a method for preparing the above-mentioned highly conductive halogen-free flame-retardant polyurethane sponge, comprising the following specific steps: S1: mixing the modified functional particles and the epoxy block in a high-speed mixer at 250 rpm for 40 minutes and then taking them out together, and then mixing them with polyether polyol, polypropylene glycol, polytetramethylene ether, deionized water, flame retardant, catalyst and additives, and stirring at 100 rpm for 35 minutes to mix evenly; S2: adding polyisocyanate and stirring at 1800 rpm for 4 minutes, placing the stirred mixture into a sponge mold, controlling the mold temperature at 32.5°C, keeping it warm for 22 hours, and washing and cutting after completion.

[0078] Comparative Example 1

[0079] The specific implementation of this comparative example is basically the same as that of Example 1, except that the polyether polyol is polyoxypropylene glycol with a functionality of 2 and a weight average molecular weight of 4000 g / mol, which is a product of the corresponding molecular weight purchased from Suzhou Senfida Chemical Co., Ltd.

[0080] Comparative Example 2

[0081] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of the highly conductive halogen-free flame-retardant polyurethane sponge, in parts by mass, include: 60.5 parts of polyether polyol, 10.8 parts of polypropylene glycol, 3.5 parts of polytetramethylene ether, 63.5 parts of polyisocyanate, 2.4 parts of deionized water, 12.5 parts of modified functional particles, 8.5 parts of flame retardant, 8.8 parts of epoxy block, 1.8 parts of catalyst, and 8.2 parts of additives.

[0082] Comparative Example 3

[0083] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the weight-average molecular weight of polypropylene glycol is 4000 g / mol, which is a product of corresponding molecular weight sold by Hai'an Petrochemical in Jiangsu Province; the polytetrahydrofuran ether is polytetrahydrofuran diol with a weight-average molecular weight of 2000 g / mol, which is a product of corresponding molecular weight sold by Shandong Deyitai New Materials Co., Ltd.

[0084] Comparative Example 4

[0085] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of the highly conductive halogen-free flame-retardant polyurethane sponge, in parts by mass, include: 42.5 parts of polyether polyol, 24.4 parts of polypropylene glycol, 11.5 parts of polytetramethylene ether, 63.5 parts of polyisocyanate, 2.4 parts of deionized water, 5.5 parts of modified functional particles, 8.5 parts of flame retardant, 2.4 parts of epoxy block, 1.8 parts of catalyst, and 8.2 parts of additives.

[0086] Comparative Example 5

[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified functional particles comprises the following steps, by mass: S1: 4.86 parts of expandable graphite and 0.22 parts of titanium dioxide are mixed and added to 120 parts of deionized water, 0.25 parts of petroleum calcium sulfonate and 1.18 parts of succinic anhydride are added, heated to 65°C, ultrasonically dispersed uniformly, stirred at a speed of 100 r / min for 3 hours, and 0.22 parts of 3-aminopropyltriethoxysilane are added dropwise 0.5 hours before the reaction to obtain pretreated particles; S2: 3.8 parts of pretreated particles and 0.65 parts of uniform The benzenetricarboxylic acid is mixed and added to 80 parts of DMF solution, stirred evenly and ultrasonically dispersed for 15 minutes to obtain a mixed solution, and then a DMF solution containing 1.75 parts of copper acetate (20 parts in total) is added dropwise to the mixed solution, the dropping temperature is 60°C, the dropping is accompanied by stirring at a speed of 200r / min, the dropping time is 1h, and after the dropping is completed, the reaction is transferred to a high-pressure reactor and heated to 125°C for insulation reaction for 16h; S3: After the reaction is completed, 0.58 parts of triethanolamine are added, mixed and stirred for 1h, the product is centrifuged and filtered, and methanol washing and 80°C vacuum drying are cycled 3 times, and the product is obtained after completion.

[0088] Comparative Example 6

[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified functional particles comprises the following steps, by mass: S1: 2.36 parts of expandable graphite and 0.72 parts of titanium dioxide are mixed and added to 120 parts of deionized water, 0.45 parts of petroleum calcium sulfonate and 1.28 parts of succinic anhydride are added, heated to 65°C, ultrasonically dispersed uniformly, stirred at a speed of 100 r / min for 3 hours, and 0.28 parts of 3-aminopropyltriethoxysilane are added dropwise 0.5 hours before the reaction to obtain pretreated particles; S2: 6.5 parts of pretreated particles and 0.35 parts of uniform Add benzenetricarboxylic acid to 80 parts of DMF solution, stir evenly and ultrasonically disperse for 15 minutes to obtain a mixed solution, then add DMF solution containing 1.18 parts of copper acetate (20 parts in total) dropwise into the mixed solution, the dropping temperature is 60°C, the dropping is accompanied by stirring at a speed of 200r / min, the dropping time is 1h, after the dropping is completed, transfer the reaction to a high-pressure reactor and heat to 125°C for 16h; S3: after the reaction is completed, add 0.31 parts of triethanolamine, mix and stir for 1h, centrifuge and filter the product, wash with methanol and vacuum dry at 80°C for 3 times, and obtain the product after completion.

[0090] Comparative Example 7

[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 50 nm; the average particle size of expandable graphite is 12 μm.

[0092] Comparative Example 8

[0093] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy block is a block copolymer of ethylene oxide and propylene oxide, and the epoxy block is a composition of BASF L42 (weight average molecular weight 1600 g / mol) and BASF L85 (weight average molecular weight 4600 g / mol), and the mass ratio of the two is 1:1.

[0094] Performance Evaluation

[0095] 1. Conductive test: The polyurethane sponges prepared in the examples and comparative examples were subjected to surface resistance tests under the following conditions: temperature 25°C, relative humidity 50%. The surface of the polyurethane sponge was tested using a surface resistance meter. The test values ​​were averaged over 10 tests and recorded in Table 1.

[0096] 2. Flame retardant test: The polyurethane sponges prepared in the examples and comparative examples were subjected to flame retardant tests with reference to standard GB / T8624-2012, and the flame retardant grade results are recorded in Table 1.

[0097] 3. Mechanical test: The tensile strength and elongation at break of the polyurethane sponges prepared in the examples and comparative examples were tested with reference to standard GB / T10654-2001. The test values ​​were averaged from 10 tests and recorded in Table 1.

[0098] 4. Waterproof test: The polyurethane sponge prepared in the embodiment and the comparative example was used to prepare a 2cm×2cm×1cm sample, and the water contact angle on its surface was tested by the sessile drop method. The test water drop size was 2.5 μL, and the test time was 10 s. The water contact angle at 10 s was calculated, and the test was continued until the water drop was completely immersed in the polyurethane sponge. The immersion time (s) was recorded. The test value was the average of 10 tests and recorded in Table 1.

[0099] 5. Aging resistance test: The polyurethane sponges prepared in the embodiments and comparative examples were placed in a constant temperature and humidity chamber at a temperature of 63°C and a relative humidity of 75% for 6 months, and their mechanical properties were tested again through performance test 3. If the tensile strength and elongation at break performance data maintained above 90% (including 90%) of the original values, they were considered qualified, otherwise they were considered unqualified. 50 groups were tested in each group, and the aging resistance qualified rate (%) = number of qualified samples / 50×100%. The test values ​​were the average of 10 tests and recorded in Table 1.

[0100] Table 1 Performance test results

[0101]

[0102] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 8 in terms of conductivity (antistatic), flame retardancy, mechanical properties, water resistance and aging resistance, which is mainly due to the combined effect of the modified functional particles, epoxy block and polyol composition added as specified in the present application; while comparative examples 1 to 8 have obvious disadvantages in the above-mentioned properties because they do not adopt the correct technical scheme specified in the present application, which further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and the technical problems solved.

Claims

1. A highly conductive halogen-free flame-retardant polyurethane sponge, characterized in that: The raw materials include, by weight: 40-50 parts of polyether polyol, 20-30 parts of polypropylene glycol, 5-15 parts of polytetramethylene ether, 50-70 parts of polyisocyanate, 1-4 parts of deionized water, 5-15 parts of modified functional particles, 5-10 parts of flame retardant, 5-10 parts of epoxy block, 1-2 parts of catalyst, and 5-15 parts of auxiliary agent; The polyether polyol is at least one of polyoxypropylene polyol, polyoxypropylene / ethylene oxide copolymer polyol, glyceryl polyether polyol, and tetrahydrofuran-propylene oxide copolymer polyol; The functionality of the polyether polyol is 3; the weight average molecular weight of the polyether polyol is 4500 to 7000 g / mol; The weight average molecular weight of the polypropylene glycol is 2000-3000 g / mol; the weight average molecular weight of the polytetramethylene ether is 1000-1500 g / mol; The polyisocyanate is at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, cyclohexane diisocyanate, and xylylene diisocyanate; The preparation method of the modified functional particles comprises the following steps: S1: adding expandable graphite and titanium dioxide to water, adding petroleum calcium sulfonate and succinic anhydride, heating to 60-70°C, ultrasonically dispersing uniformly, stirring at a speed of 60-120 r / min for reaction for 2-3 hours, and adding 3-aminopropyltriethoxysilane dropwise 0.5 hours before the reaction to obtain pretreated particles; S2: adding the pretreated particles and trimesic acid to a DMF solution, stirring uniformly, and ultrasonically dispersing for 10-15 minutes to obtain a mixed liquid, then the DMF solution containing copper acetate is added dropwise to the mixed solution, the dropping temperature is 50-60°C, the dropping is accompanied by stirring at a speed of 200-300r / min, the dropping time is 1-1.5h, after the dropping is completed, the reaction is transferred to a high-pressure reactor and heated to 120-130°C for 14-20h; S3: after the reaction is completed, triethanolamine is added, the mixture is stirred for 0.5-1h, the product is centrifuged and filtered, and the methanol washing and 80-90°C vacuum drying are repeated for multiple times, and the product is obtained after completion; The mass ratio of expandable graphite, titanium dioxide, calcium petroleum sulfonate, succinic anhydride and 3-aminopropyltriethoxysilane is (2-3): (0.5-1): (0.4-0.8): (1-1.5): (0.1-0.3); The mass ratio of the pretreated particles, trimesic acid, copper acetate and triethanolamine is (3.5-4): (0.4-0.8): (1.2-2): (0.4-0.6); The flame retardant is a composition of ammonium polyphosphate and zinc borate; the mass ratio of the ammonium polyphosphate to the zinc borate is (4-8): (2-4).

2. The highly conductive halogen-free flame-retardant polyurethane sponge according to claim 1, characterized in that: The mass ratio of the polyether polyol, polypropylene glycol, polytetramethylene ether and polyisocyanate is (4-4.5): (2-2.5): (1-1.5): (5.5-6.5).

3. The highly conductive halogen-free flame-retardant polyurethane sponge according to claim 2, characterized in that: The polytetrahydrofuran ether is polytetrahydrofuran diol.

4. The highly conductive halogen-free flame-retardant polyurethane sponge according to claim 3, characterized in that: The polyisocyanate is 2,4'-diphenylmethane diisocyanate.

5. The highly conductive halogen-free flame-retardant polyurethane sponge according to claim 4, characterized in that: The average particle size of the titanium dioxide is 10-30 nm; the average particle size of the expandable graphite is 4-8 μm.

6. The highly conductive halogen-free flame-retardant polyurethane sponge according to claim 5, characterized in that: The epoxy block material is a block copolymer of ethylene oxide and propylene oxide; the epoxy block material is a composition of an epoxy block material with a weight average molecular weight of 1000-2000 g / mol and an epoxy block material with a weight average molecular weight of 4000-5000 g / mol.

7. The highly conductive halogen-free flame-retardant polyurethane sponge according to claim 6, characterized in that: The mass ratio of the epoxy block with a weight average molecular weight of 1000-2000 g / mol to the epoxy block with a weight average molecular weight of 4000-5000 g / mol is (1-1.5):(3-4).

8. The highly conductive halogen-free flame-retardant polyurethane sponge according to claim 7, characterized in that: The auxiliary agent at least includes an auxiliary foaming agent and a surfactant; the mass ratio of the foaming agent to the surfactant is (0.5-2): (6-10).

9. A method for preparing the highly conductive halogen-free flame-retardant polyurethane sponge according to any one of claims 1 to 8, characterized in that: The method comprises the following specific steps: S1: mixing the modified functional particles and the epoxy block in a high-speed mixer at 200-300 rpm for 30-40 minutes, taking them out together, and then mixing them with polyether polyol, polypropylene glycol, polytetrahydrofuran ether, deionized water, flame retardant, catalyst and auxiliary agent, stirring at a speed of 60-120 rpm for 20-40 minutes to mix evenly; S2: adding polyisocyanate and stirring at a speed of 1500-2000 rpm for 3-5 minutes, placing the stirred mixture into a sponge mold, controlling the mold temperature at 30-35°C, keeping the temperature for 20-25 hours, washing and cutting after completion, and obtaining the sponge.

10. Use of the highly conductive halogen-free flame-retardant polyurethane sponge according to any one of claims 1 to 9 in electronic devices, electromagnetic interference shielding, electrostatic discharge protection, sensor devices and smart textiles.

Citation Information

Patent Citations

  • Preparation method of wave-absorbing composite material

    CN104629680A

  • Preparation method of polypropylene-grafted graphene oxide composite material

    CN106009282A

  • Graphene sponge material and preparation method thereof

    CN107698965A

  • Porous copper oxide microsphere / multilayer graphene composite material, and preparation method thereof

    CN108346782A

  • Preparation method for oil absorption material

    CN109265732A